Post-Keynesian growth theory and the supply side: a feminist approach - Mark Setterfield (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2023)
Post-Keynesian macrodynamics is designed to extend the role of demand in the determination of real economic outcomes beyond the short run. The purpose of this paper is to highlight the importance of supply-side considerations in demand-led growth. Building on existing features of the supply side in post-Keynesian growth theory, three new developments are highlighted: human capital accumulation, the social reproduction of labour, and the supply-side link between distribution and growth. These new developments are shown to yield new insights into the established themes of reconciling demand and supply in the theory of long-run growth, and the relationship between distribution and growth. Furthermore, the feminist macro model used to explore the social reproduction of labour is shown to be a potential general framework for synthesizing these insights.
Keywords: B54; E11; E12; O41; 330; demand-led growth; potential rate of growth; technical change; human capital; human capacities; care-giving